PROSES PENANAMAN NILAI-NILAI KARAKTER DALAM PEMBELAJARAN BIOLA DI SD BUDI MULIA DUA YOGYAKARTA - Normalita, Adityas; Hartono, Hartono (Catharsis, 2016)
This research aims to understand: (1) a learning process the viola di primary school budi mulia two jogjakarta; (2) the process of planting the values of character that was found at the time of learning the viola di primary school budi mulia two yogyakarta .This research adopting both interdisiplin in the form of the qualitative study with the method of analysis deskritif the process of planting nilai- nailai character, data collection technique uses observation , interviews and document the study.The results of the study obtained that: (1) there are learning violin has been based on the process has fulfilled procedure of 3 domain the phase early, stage stuffing and the cover.In addition teachers also already have a syllabus in every levels, (2) The process of planting values character is implanted early to their students primary school budi mulia two yogyakarta.Through learning violin indirectly students have values character identified through learning violin.Values character that was found in learning violin in primary schools budi mulia two yogyakarta is; 1; value religious; 2.value disipli; 3; value tolerance; 4.value of this trait; 5.value love of the land water;